r=2; (h,k)=(0,2)

*A circle centered at (h, k) with radius "r" is given by *

*(x - h) ^{2} + (y - k)^{2} = r^{2}*

**~~~~~~~~~~~**^{ }

Here h = 0 , k = 2, r = 2

Thus,

(x – 0)

^{2}+ (y – 2)

^{2}= 2

^{2}

Or

**x**^{2}+ (y – 2)^{2}= 4-
CREATE FREE ACCOUNT
- Access thousands of free resources from expert tutors
- Comment on posts and interact with the authors
- Ask questions and get free answers from tutors
- View videos, take interactive quizzes, and more!

- Become a Student
- Become a Student
- Sign In

r=2; (h,k)=(0,2)

Tutors, please sign in to answer this question.

*A circle centered at (h, k) with radius "r" is given by *

*(x - h) ^{2} + (y - k)^{2} = r^{2}*

Here h = 0 , k = 2, r = 2

Thus,

(x – 0)

Or